Unraveling the Photoprotective Response of Lichenized and Free-Living Green Algae (Trebouxiophyceae, Chlorophyta) to Photochilling Stress - Míguez, Fátima; Schiefelbein, Ulf; Karsten, Ulf; García-Plazaola, José I.; Gustavs, Lydia (Frontiers in Plant Science, 2017)
Lichens and free-living terrestrial algae are widespread across many habitats and develop successfully in ecosystems where a cold winter limits survival. With the goal of comparing photoprotective responses in free-living and lichenized algae, the physiological responses to chilling and photochilling conditions were studied in three lichens and their isolated algal photobionts together as well as in a fourth free-living algal species. We specifically addressed the following questions: (i) Are there general patterns of acclimation in green algae under chilling and photochilling stresses? (ii) Do free-living algae exhibit a similar pattern of responses as their lichenized counterparts? (iii) Are these responses influenced by the selection pressure of environmental conditions or by the phylogenetic position of each species? To answer these questions, photosynthetic fluorescence measurements as well as pigment and low molecular weight carbohydrate pool analyses were performed under controlled laboratory conditions. In general, photochemical efficiency in all free-living algae decreased with increasing duration of the stress, while the majority of lichens maintained an unchanged photochemical activity. Nevertheless, these patterns cannot be generalized because the alga Trebouxia arboricola and the lichen Ramalina pollinaria (associated with Trebouxia photobionts) both showed a similar decrease in photochemical efficiency. In contrast, in the couple Elliptochloris bilobata-Baeomyces rufus, only the algal partner exhibited a broad physiological performance under stress. This study also highlights the importance of the xanthophyll cycle in response to the studied lichens and algae to photochilling stress, while the accumulation of sugars was not related to cold acclimation, except in the alga Elliptochloris bilobata. The differences in response patterns detected among species can be mainly explained by their geographic origin, although the phylogenetic position should also be considered, especially in some species.